2022
DOI: 10.1021/jacs.2c04822
|View full text |Cite
|
Sign up to set email alerts
|

Ketone–Olefin Coupling of Aliphatic and Aromatic Carbonyls Catalyzed by Excited-State Acridine Radicals

Abstract: Ketone–olefin coupling reactions are common methods for the formation of carbon–carbon bonds. This reaction class typically requires stoichiometric or super stoichiometric quantities of metal reductants, and catalytic variations are limited in application. Photoredox catalysis has offered an alternative method toward ketone–olefin coupling reactions, although most methods are limited in scope to easily reducible aromatic carbonyl compounds. Herein, we describe a mild, metal-free ketone–olefin coupling reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…The ESI‐HRMS detected TEMPO adducts with both 2 aa and 2 ba corroborate with the former statement (Figure 7D). Entry 4 g (Figure 4) provides an authentication for a radical clock experiment, with no open chain products obtained [7, 40] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESI‐HRMS detected TEMPO adducts with both 2 aa and 2 ba corroborate with the former statement (Figure 7D). Entry 4 g (Figure 4) provides an authentication for a radical clock experiment, with no open chain products obtained [7, 40] …”
Section: Resultsmentioning
confidence: 99%
“…Entry 4 g (Figure 4) provides an authentication for a radical clock experiment, with no open chain products obtained. [7,40] With this information in hand, a plausible reaction mechanism was outlined for the benzylation process (Figure 8). Once 2 a gets oxidized by the excited photocatalyst PC1, benzylic radical 2 a' is formed which is stabilized by the delocalization into the phenyl ring.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the Yoon group revealed that Ru(bpy)3Cl2 serves as an efficient photocatalyst for generating radical anions from activated alkene-aryl enones under visible light irradiation, and developed efficient intra-and intermolecular [2+2] enone cycloadditions (25,26). Quite recently, Polyzos (27) and Nicewicz (28) reported breakthrough discoveries involving the application of photoexcited reduced species of [Ir(ppy)2(dtb-bpy)]PF6 and acridinum salt as super SET donors towards the reduction of styrenes and conjugated alkenes to the corresponding radical anions upon multiphoton excitation using stoichiometric N,N-diisopropylethylamine (DIPEA) as a sacrificial electron donor. The resultant nucleophilic radical anions can then be added to ketones in an intra-or intermolecular manner, followed by further SET-reduction and protonation to yield reductive hydrofunctionalization products.…”
Section: Introductionmentioning
confidence: 99%
“…9 In 2019, the Jamison group reported intermolecular ketyl−olefin coupling by using p-terphenyl as the photoredox catalyst. 10 Related photocatalytic ketyl−olefin coupling processes have also been reported by Rueping, 11 Glorius, 12 Doyle, 13 Nicewicz, 14 Yoon, 15 and others. 16 The electrochemical generation of ketyl radicals has also been demonstrated as an alternative to stochiometric reductants for the generation of ketyl radicals.…”
mentioning
confidence: 99%